2019
DOI: 10.1002/phar.2220
|View full text |Cite
|
Sign up to set email alerts
|

Vasoactive Agent Use in Septic Shock: Beyond First‐Line Recommendations

Abstract: Septic shock is a life‐threatening disorder associated with high mortality rates requiring rapid identification and intervention. Vasoactive agents are often required to maintain goal hemodynamics and preserve tissue perfusion. However, guidance regarding the proper administration of adjunct agents for the management of septic shock is limited in patients who are refractory to norepinephrine. This review summarizes vasopressor agents and describes the nuanced application of these agents in patients with septic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(14 citation statements)
references
References 100 publications
(217 reference statements)
0
13
0
1
Order By: Relevance
“…ANG II also enhances the release of NE from sympathetic nerve endings (6). The exogenous application of ANG II improves the sensitivity of blood vessels to catecholamines, constricts the glomerular efferent arteries, increases the glomerular perfusion pressure, and elevates the glomerular filtration rate (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…ANG II also enhances the release of NE from sympathetic nerve endings (6). The exogenous application of ANG II improves the sensitivity of blood vessels to catecholamines, constricts the glomerular efferent arteries, increases the glomerular perfusion pressure, and elevates the glomerular filtration rate (20)(21)(22).…”
Section: Discussionmentioning
confidence: 99%
“…Several recent articles have described the detrimental effects of catecholamines and optimal use of alternative vasopressors such as vasopressin and angiotensin II. [19][20][21][22][23] However, despite their appeal, studies have not demonstrated conclusive benefits of alternative vasopressors over adrenergic agents. 5,19 Although retrospective studies have suggested a benefit of early vasopressin initiation, [24][25][26] a large interventional study did not find a benefit in kidney failure-free days or mortality with this approach.…”
Section: Discussionmentioning
confidence: 99%
“…Vasopressin reduces the dose of catecholamine vasopressors, but does not appear to affect patient mortality [2]. It is often used as a replacement dose after initiation of norepinephrine [29].…”
Section: Management/treatmentmentioning
confidence: 99%